The Scientific-Didactic Principles Theory for the Teaching of Geography, History and Social Sciences: A New Model of Knowledge - Javier Contreras García; Salvador Mateo Arıas Romero (Sakarya University Journal of Education)
In 1993, Dr. Antonio Luis García Ruiz (University of Granada, Spain) investigated the development of the Theory of Scientific-Didactic Principles, a new didactic model based on the contextualization of the object studied through the use of 8 principles (then will be 10), and applied to the subjects of Geography and History in the field of education. After more than 20 years of work, the theory has produced more than 80 publications between: articles, books and doctoral Tesis, now entering new fields such as the History of Art. This article is based on the knowledge of this theory at the international level and a summary of the results of this work.